Cervical disc deformation during flexion-extension in asymptomatic controls and single-level arthrodesis patients - Anderst, William; Donaldson, William; Lee, Joon; Kang, James (Journal of orthopaedic research, 2013)
The aim of this study was to characterize cervical disc deformation in asymptomatic subjects and single‐level arthrodesis patients during in vivo functional motion. A validated model‐based tracking technique determined vertebral motion from biplane radiographs collected during dynamic flexion–extension. Level‐dependent differences in disc compression–distraction and shear deformation were identified within the anterior and posterior annulus (PA) and the nucleus of 20 asymptomatic subjects and 15 arthrodesis patients using a mixed‐model statistical analysis. In asymptomatic subjects, disc compression and shear deformation per degree of flexion–extension progressively decreased from C23 to C67. The anterior and PA experienced compression–distraction deformation of up to 20%, while the nucleus region was compressed between 0% (C67) and 12% (C23). Peak shear deformation ranged from 16% (at C67) to 33% (at C45). In the C5–C6 arthrodesis group, C45 discs were significantly less compressed than in the control group in all disc regions (all p ≤ 0.026). In the C6–C7 arthrodesis group, C56 discs were significantly less compressed than the control group in the nucleus (p = 0.023) and PA (p = 0.014), but not the anterior annulus (AA; p = 0.137). These results indicate in vivo disc deformation is level‐dependent, and single‐level anterior arthrodesis alters the compression–distraction deformation in the disc immediately superior to the arthrodesis. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31:1881–1889, 2013